2003
DOI: 10.1097/00004872-200305000-00011
|View full text |Cite
|
Sign up to set email alerts
|

The Study on Cognition and Prognosis in the Elderly (SCOPE)

Abstract: . Study on cognition and prognosis in the elderly (SCOPE). Blood Pressure 1999; 8: 177-183.The Study on COgnition and Prognosis in the Elderly (SCOPE) is a multicentre, prospective, randomized, double-blind, parallel-group study designed to compare the effects of candesartan cilexetil and placebo in elderly patients with mild hypertension. The primary objective of the study is to assess the effect of candesartan cilexetil on major cardiovascular events. The secondary objectives of the study are to assess the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
204
0
16

Year Published

2003
2003
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,259 publications
(224 citation statements)
references
References 41 publications
4
204
0
16
Order By: Relevance
“…The analysis of secondary endpoints demonstrated a fall in total mortality by 39%, in cardiovascular mortality by 37%, and in prevention of heart failure by 40%, favouring the losartan group relative to the atenolol group. The benefit of an ARB on cerebrovascular protection has been confirmed by the SCOPE study, 71 in which non-fatal stroke prevalence was significantly lower in the group receiving candesartan. The benefits of the ARB took place in association with better BP control, which could explain part of the protective effect.…”
Section: Cardiovascular Protection In Type 2 Diabetic Subjectsmentioning
confidence: 81%
See 1 more Smart Citation
“…The analysis of secondary endpoints demonstrated a fall in total mortality by 39%, in cardiovascular mortality by 37%, and in prevention of heart failure by 40%, favouring the losartan group relative to the atenolol group. The benefit of an ARB on cerebrovascular protection has been confirmed by the SCOPE study, 71 in which non-fatal stroke prevalence was significantly lower in the group receiving candesartan. The benefits of the ARB took place in association with better BP control, which could explain part of the protective effect.…”
Section: Cardiovascular Protection In Type 2 Diabetic Subjectsmentioning
confidence: 81%
“…66 Cardiovascular protection with ARBs has been studied in Evaluation of Losartan in The Elderly II (ELITE II), 67 Valsartan Heart Failure Trial (ValHeFT), 68 LIFE 69,70 and Study on Cognition and Prognosis in the Elderly (SCOPE). 71 The first two studies were performed in patients with heart failure and have shown promising results, but the absence of difference in cardiovascular outcome between ARBs and placebo or amlodipine in RENAAL 4 and IDNT 5 was initially frustrating for some analysers. A meta-analysis of the events observed in the three studies (RENAAL, IDNT and IRMA 2) devoted to the role of ARBs in diabetic nephropathy has also been published, 72 showing that, although for cardiovascular death no significant difference was found among ARBs and placebo, a positive and significant difference was found for non-fatal cardiovascular events.…”
Section: Cardiovascular Protection In Type 2 Diabetic Subjectsmentioning
confidence: 99%
“…Both amlodipine and candesartan have been shown to reduce risk of stroke in clinical studies. 25,26) These results led us to postulate that benidipine would be safe in hypertensive patients with impaired CBF autoregulation, because it preserves the function of CBF autoregulation in the therapy of blood pressure control. In addition, normalization of dysautoregulation of CBF may be one of the important mechanisms underlying the protection by benidipine against cerebrovascular injury.…”
Section: Discussionmentioning
confidence: 99%
“…Nello studio AL-LHAT [23] è stato osservato che nei soggetti d'età >65 anni l'effetto dei calcioantagonisti e degli ACEinibitori era sovrapponibile nel beneficio a quello della terapia convenzionale con diuretico e/o betabloccante. Tuttavia, i pazienti ipertesi di 55-80 anni del trial LIFE [43,51] e portatori di ipertrofia ventricolare sinistra, come quelli di 70 e più anni dello SCOPE [50], hanno mostrato una minore incidenza di eventi cardiovascolari, soprattutto di ictus ed endpoint composito [51], con antagonisti dei recettori di angiotensina II, specificatamente losartan e candesartan, piuttosto che con atenololo o altre classi di farmaci. Nello studio Syst-Eur, disegnato per valutare il rischio d'ictus e di mortalità cardiovascolare sulla popolazione anziana europea, l'aumento della variabilità della PAS notturna risultava un fattore di rischio indipendente per ictus [29] nel gruppo placebo, non in quello in trattamento attivo.…”
Section: ) Pazienti Anzianiunclassified